Webster's new world dictionary for young readers - Guralnik, David B.; Guralnik, David B.; Rogoff, Anita S. (New York : SIMON AND SCHUSTER, 1983)
Is such a book. It is the first in a series of carefully coordinated dictionaries that have been prepared to serve the needs of students from the early grades through college and beyond. The vocabulary list of the Basic School Edition was selected from the vast citation file of the Webter's New World Dictionary.
Contents 1. Foreword 2. A Story of some American Words 3. How to use your dictionary 4. References of the American Languaje 5. Atlas
Incluye mapas a colores
Incluye vocabulario
Keywords: ENCICLOPEDIA Y DICCIONARIOS; ENCICLOPEDIA - INGLÉS